Maxwell hybrid nanofluid flow towards a stagnation point on a stretching/shrinking inclined plate with radiation and nanoparticles shapes effect - Nadhira Azreen, Azmi; Mohd Rijal, Ilias; Siti Shuhada, Ishak; Roselah, Osman; Abdul Rahman, Mohd Kasim (Semarak Ilmu Publishing, 2024)
The current study explored the Maxwell hybrid nanofluid on mixed convective radiative over a stretching/ shrinking inclined plate with nanoparticles shapes effect. Copper and aluminum oxide were introduced to sodium alginate as a base fluid to formulate the problem and the effect of shape factor is examined by considering spherical, bricks, cylindrical and platelet nanoparticles. Using similarity transformation, the governing nonlinear partial differential equations of the Maxwell hybrid nanofluid are converted to nonlinear ordinary differential equations. Then, they are solved numerically using the Keller Box method and the system issolved by using Fortran software. The physical behavior of controlling factors on velocity and temperature profiles as well as skin friction and local Nusselt number are depicted graphically and tabulated. The various shapes of nanoparticles produce considerable differences in the Maxwell hybrid nanofluid’s velocity and temperature functions. For all parameters, nanoparticles shape with the highest Nusselt number is platelet, followed by cylindrical, bricks and spherical. The findings of this study will provide information and knowledge in mathematics for mathematicians who interested in future research on Maxwell hybrid nanofluid.